Small farmers secure food : survival food security, the world's kitchen & the crucial role of small farmers - Falvey, J. Lindsay ([Songkhla] : Thaksin University Press, 2010)
"This is a simple book. It argues for a return of two critical values in international development, the securing of food for a minimal level of existence and acknowledgement of the vital role of small farmers in that basic level of food security. The diluted forms of these once central pillars of assistance and government have weakened them to the point that international development efforts are now increasing the risks of starvation in the world. Some of the facts and arguments presented here will be counterintuitive to conventionally trained functionaries, and so illustrative data and information is provided in support of forgotten yet enduring axioms"--P.1.
Contents: Ch. 1 Introductory words -- Ch. 2 Food, farmers and fallacy -- Ch. 3 Securing enough food to survive -- Ch. 4 Forgotten food producers: small farmers -- Ch. 5 Why bit the hand that feeds? -- Ch. 6 Good governance starts with food security -- Ch. 7 From criticism to action: refocusing on small farmers and food security -- Ch. 8 Practical food security from small farmers.
"In association with Institute for International Development, Australia."
Keywords: Food security; Farms, Small